Reviving Ancient Ephesus: An AI-Powered Virtual Realm - Denker, Ahmet; Yurt, Arda; Gormus, Ayberk; Piker, Can Mert; Gunduz, Eray (Institute of Electrical and Electronics Engineers Inc., 2025)
The rise of artificial intelligence (AI) has ushered in a new era of interactive experiences of virtual antiquity, where virtual characters play a central role in engaging visitors at reconstructed cultural heritage (CH) sites. This study explores the intersection of Virtual Reality (VR) and AI-driven character creation in enriching the virtual experience of ancient Ephesus at its peak. By integrating lifelike AI-powered avatars, imbued with personality and emotion, we try to showcase that it is possible to bridge the gap between visitors and digital heritage environments. These intelligent avatars, driven by sophisticated AI technologies serve as interactive guides, fostering immersive and intuitive engagement. They not only respond to user interactions but also adapt their behavior dynamically, enabling deeper, more personalized storytelling experiences. At the core of this innovation is the synergy between AI technologies such as Natural Language Processing (NLP) and machine learning, which empower avatars to comprehend and generate human-like responses, recognize emotions, and react in real time. This transformative approach enhances user engagement by offering interactive narratives that bring the history of ancient Ephesus to life. Beyond technical implementation, effective character design plays a crucial role in audience immersion. Our approach incorporates creation of life-like avatars and storytelling principles, ensuring that avatars possess distinct personalities, motivations, and rich backstories that resonate emotionally with users. Through expressive dialogue, gestures, and nuanced interactions, these AIdriven characters transcend traditional virtual experiences, creating a compelling, memorable journey through the streets of ancient Ephesus. This work demonstrates the potential of AIdriven avatars in digital heritage applications, offering a glimpse into the future of cultural and historical heritage where historical reconstructions become not just visual representations, but living, interactive worlds. © 2025 IEEE.
11th International Conference on Virtual Reality, ICVR 2025 -- 9 July 2025 through 11 July 2025 -- Wageningen -- 213172
Keywords: Ai-Driven Avatars; Artificial Intelligence (Ai); Ephesus; Immersive Virtual Experience (Ive); Reconstruction (3D); Virtual Reality (Vr)